SERVICE QUALITY FACTORS AFFECTING SATISFACTION ON APARTMENT RENTAL SERVICES IN CHATUCHAK DISTRICT, BANGKOK - Aupara, Kitiphong; Phumpa, Prawit; Suanchimplee, Tassanee; Satchapappichit, Sruangporn (Journal of MCU Nakhondhat, 2025)
This research aims to compare tenant satisfaction on apartment rental services in Chatuchak District, Bangkok, classified by decision-making behaviour, and to study service quality factors affecting tenant satisfaction on apartment rental services. The study employs a quantitative research methodology, with the sample group consisting of individuals currently renting apartments in Chatuchak District for a minimum rental period of six months. Using Cochran’s formula, the sample size was calculated to be 384 participants. The research instrument utilized was a questionnaire, and data collection was conducted through online questionnaires. The statistical methods used for data analysis include descriptive statistics such as percentage, mean, and standard deviation, as well as inferential statistics using One-Way ANOVA and Multiple Regression Analysis. The research results showed that the service quality factor in terms of assurance was the most important and tenants’ satisfaction varied significantly based on rental decision-making behaviour factors such as rental duration, average monthly rental price for accommodation, purpose of renting, sources of information, influential individuals, and number of tenants at the 0.05 level. Service quality factors, including tangibility, reliability, assurance, and empathy, had a statistically significant impact on customer satisfaction at the 0.05 level. The results of this research can be applied to improve service quality in the apartment rental business.